Comparison of the Influence of Motivation for Foreign Tourists' Visits to Bali with the Inauguration of the Garuda Wisnu Kencana Statue - Supina; Rustono Farady Marta; Cut Meutia Karolina (International Journal of Applied Sciences in Tourism and Events, 2022)
There is a growing expectation for the iconic statue to emerge as a tourism icon, particularly in Bali, Indonesia; following the completion of the Garu-da Wisnu Kencana Statue in 2018. Therefore, this quantitative study was car-ried out to answer the two key research questions; Are potential tourists aware of the presence of this new landmark after the development and whether there is an influence on motivation to visit, particularly for foreign tourists? The study was conducted using an online survey that was sent to 80 foreign tourists from all around the world. The findings revealed that the majority of respondents in this survey were uninformed of the statue's presence, and that if they were aware of its presence, it had an impact on their desire to visit Bali. This makes it critical to raise public awareness about the Garuda Wisnu Kencana Statue, which located at the Garuda Wisnu Kencana Cultural Park in Bali, Indonesia and suggested that the presence of Garuda Wisnu Kencana Statue can be op-timally used as a significant marketing tools by Indonesian Ministry of Tourism. Theoretical implications include summarizing the key elements of a tourism destination with a tourism icon that attracts potential tourists. Practical implica-tions include presenting measurement on steps to maximize the presence of a tourism icon with a variety of expectations from potential tourists.